Analisis Determinan Cadangan Devisa di Indonesia - Bagus Adhitya (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to analyze the effect of exports, imports and inflation rates on foreign exchange reserves in Indonesia. This type of research is quantitative. This research method uses multiple linear regression with the Ordinary Least Square model. The results showed that exports had a positive and significant effect on foreign exchange reserves in Indonesia at 2011-2018. Imports have a negative and significant effect on foreign exchange reserves in Indonesia at 2011-2018. The inflation rate has no positive effect on foreign exchange reserves in Indonesia in 2011-2018. This finding implies that the government must increase exports abroad to suppress imports of foreign products.